Generation of induced pluripotent stem cells, KCi005-A derived from a female with Parkinsońs disease and homozygous for the PINK1 variant c.1366C > T, p.Gln456* - Lasse Jonsgaard Larsen; Lena Elisabeth Hjermind; Lisbeth Birk Møller (Stem Cell Research, 2024)
Disease causing variants in several genes including PINK1 have been identified in hereditary Parkinsońs disease (PD). The mechanism behind this neuronal degeneration is not clarified but it is assumed that mitochondrial dysfunction, e.g. oxidative stress, might be involved. Here we describe the generation of an induced pluripotent stem cell clone (iPSC) KCi005-A from a female PD patient homozygous for the disease-causing variant c.1366C > T, p.Gln456* in PINK1. To obtain the iPSC clone we use a non-integrative self-replicating RNA vector. The clone might be a useful resource to study pathogenic mechanisms not only restricted to this variant.